Online Teaching During COVID-19: Exploration of Challenges and Their Coping Strategies Faced by University Teachers in Pakistan - Sahito, Zafarullah; Shah, Sayeda Sapna; Pelser, Anna-Marie (Frontiers in Education, 2022)
The provision and practice of an online environment have become the main challenge for many institutes including universities during the COVID-19 pandemic. However, the use of an online learning system was used by the majority of the teachers through an understanding of the adoption of ICT with the major challenges faced by them during the teaching-learning process. It has been found through this study that the teachers are lacking in ICT literacy. Therefore, they are facing online classroom management, and connectivity issues throughout their journey during COVID-19. This study aims to explore the challenges and coping strategies faced by university teachers during the pandemic of COVID-19. A qualitative research method with a case study approach was used to get an in-depth understanding of the phenomenon of online teaching during COVID-19. Interviews were collected from eleven teacher educators of the university. After analyzing the data, nine themes were generated with major findings i.e. connectivity issues; online teaching methods and techniques; learning environment for online teaching and learning; and challenges faced by teachers. The study findings are a good sought of addition and contribution for the university policymakers to evaluate, influence and ensure the successful implementation of the e-learning system. Additionally, it is a suggestion for the university management to arrange some workshops or training programs for teacher educators to improve productivity and performance during their online teaching.